EFFECT OF SHORT STARVATION AND REFEEDING ON GROWTH, BODY COMPOSITION, AND DIGESTIVE ENZYMES ACTIVITIES IN YELLOW RASBORA (Rasbora lateristriata Blkr.) - U. Susilo; Y. Sistina; E.S. Wibowo; A. Nuryanto (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Digestive enzyme activities of Yellow Rasbora (Rasbora lateristriata) had been reported, but only focused on a daily feeding strategy. The effect of starvation and refeeding on the growth, body composition, and digestive enzyme activities in Yellow Rasbora has never been reported. This study aimed to know the most efficient feeding strategy for growth, body composition, and digestive enzyme activities of Yellow Rasbora. The experiment was conducted in 20 aquariums using two months old fingerling. Four different feeding strategies were tested; twice feeding a day, one-day starvation and six days refeeding, two days starvation and five days refeeding, and four days starvation and ten days refeeding. The result showed that different feeding strategies had no significant effect on all growth parameters. The result proved that Yellow Rasbora could compensate for starvation through absolute growth, with the highest value achieved in two days of starvation and five refeeding. No significant value was also observed on crude protein, and lipid contents indicate that starvation does not affect the utilization of protein and lipid reserves. This result was consistent with fish condition factors which did not differ among treatments. The feeding strategy did not significantly affect total protease, trypsin, and amylase activities, but significantly affected chymotrypsin, lipase, and alkaline phosphatase activities. All parameter indicated that two days starvation and five days refed duration showed similar values to daily feeding. Therefore, it is concluded that two days starvation and five days refeeding method is the most efficient feeding strategy for Yellow Rasbora cultivation.